Pendidikan Sebagai Pilar Penguat Dinamika Integrasi Nasional - Rr. Maylinda Divarukmi Kusuma; Nadia Khayana Tantri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Education has a strategic role as a means of character formation, the dissemination of national values, and the strengthening of national integration in a multicultural society. In the context of Indonesia, which is rich in ethnic, cultural, and religious diversity, education functions as a medium for the transformation of Pancasila values and nationalism. This article aims to analyze the role of education in strengthening the dynamics of national integration through the literature review method of various scientific articles in the field of Civic Education (PKn). This research reveals that education and teachers, parents, and the community contribute to internalizing the values of tolerance, diversity, and national awareness. Citizenship, participatory, and inclusive education is the key to the success of dynamic and sustainable national integration. This article also suggests the enforcement of character education and the modification of the curriculum based on Pancasila values to strengthen the unity of the nation.